Dampak Pemahaman Keagamaan dan Kemampuan Literasi Media Terhadap Sebaran Berita Hoax di Komunitas Surabaya Mengaji - Ellyda Retpitasari (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2022)
The research analysis is related to the influence of religious understanding and media literacy skills on the tendency to spread hoax news in the Surabaya Mengaji Community. This study uses a quantitative research approach, with a population of participants in the Sunday routine study at the Jami Mecca Bendul Merisi Mosque in Surabaya under the auspices of the Surabaya Mengaji Community. for statistical data analysis using the Yule's Q statistical formula. Based on the results of Yule's Q statistical calculations it shows that the correlation of religious understanding to the spread of hoax news is -0.178, which means it has a